Customs, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (H. Strong Ltd., 2011)
A picture of Customs, Port of Spain. In this picture docked boats and the pier can be seen. There is a note in handwriting on the postcard that reads "All large steamers and small come in here from all over the world".
Colour: Black and White; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Boats and boating--Trinidad and Tobago; Harbors--Trinidad and Tobago; Customhouses--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain